Cyanophyceaen and Chlorophyceaen flora of Sikkim Himalayas, India - Kumar, Satendra; Suseela, M. R.; Toppo, Kiran (Ecoprint: An International Journal of Ecology, 2010)
The present paper enumerates 30 taxa of fresh water algae, in which 18 belong to the class Cyanophyceae, order Chroococcales and 12 Chlorophyceaen taxa, orders Cladophorales, Oedogoniales, Chaetophorales, Zygenmatales and Ulotrichales. Species were identified from collected samples of high altitudinal zones of Sikkim Himalayas. All taxa have been reported for the first time from the study area. Key words: Cyanophyceae; Chlorophyceaen; Sikkim Himalayas doi: 10.3126/eco.v12i0.3195 Ecoprint: An International Journal of Ecology 12: 35-42, 2005